Noninvasive Evaluation of Myocardial Work in Patients with Chronic Kidney Disease Using Left Ventricular Pressure-Strain Loop Analysis - Xiaohua Liu (Diagnostics, 2022)
(1) Objective: To evaluate myocardial injury by observing the different parameters of global myocardial work (MW) by left ventricular pressure-strain loop (PSL) analysis in patients with chronic kidney disease (CKD). (2) Methods: According to the left ventricular mass index, the study patients with CKD were further divided into two groups: the left ventricular normal group (CKDN-LVH, 59) and left ventricular hypertrophy group (CKDLVH, 46). Thirty-three healthy controls (CON) matched in age and sex with the CKD group were recruited. The routine ultrasonic parameters were obtained by routine TTE, and the strain index and different parameters of the left ventricular MW were obtained by dynamic image offline analysis. (3) Results: This study found that (1) compared with the CON group, the CKDN-LVH group had a significantly increased global waste work (GWW) and significantly decreased global work efficiency (GWE), the GWW further increased, and GWE further decreased in the CKDLVH group. There was no significant change in the global work index (GWI) and global constructive work index (GCW) in the CKDN-LVH group, but the GWI and GCW in the CKDLVH group were significantly increased. (2) According to the grouping analysis of systolic blood pressure (SBP), we found that the GWW increased and GWE decreased in CKD patients with an elevated SBP. (3) Correlation analysis showed that the increase of the peak strain dispersion, SBP, and left ventricular mass index and the decrease of the estimated glomerular filtration rate were significantly correlated with the decrease of the GWE and the increase of the GWW. (4) Receiver operating characteristic curve analysis showed that the area under the curve (AUC) of myocardial damage induced by the GWE and GWW in the CKD group and CON group was higher than that of left ventricular global longitudinal strain (AUCs: 0.87 and 0.878 versus 0.72, respectively). (4) Conclusions: Noninvasive left ventricular PSL analysis can be used to evaluate the global MW in patients with CKD. The study justified the role of GWW in the noninvasive assessment of myocardial function in patients with CKD.